2023
DOI: 10.1063/5.0169934
|View full text |Cite
|
Sign up to set email alerts
|

Application of heliox for optimized drug delivery through respiratory tract

Umar Farooq,
Hafiz Hamza Riaz,
Adnan Munir
et al.

Abstract: Understanding the transportation and deposition (TD) of inhaled particles in the upper respiratory tract is crucial for predicting health risks and treating pulmonary diseases. The available literature reports highly turbulent flow in the extrathoracic (ET) region during normal breathing, which leads to higher deposition of the drug aerosol in this region. To improve the targeted deposition of inhaled drugs, in the tracheobronchial airways, it is essential to understand the flow and particle transport dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The Lagrangian approach is used to simulate the particle TD in the lung airways. The dynamics of each particle are controlled through the force balance equation: d u⃗ p d t = F D false( u⃗ u⃗ normalp false) + g⃗ ρ p false( ρ normalp ρ false) where u and u p represent the velocity of continuous and discrete phases, respectively, g is the gravitational acceleration, ρ p is particle density, which is taken as 1100 kg/m 3 . F D ( u⃗ – u⃗ p ) represents the drag force per particle mass, and the F D for the spherical particle is determined using the following relation: F D = 1 2 C D π d p 2 4 ρ false( v⃗ normalp v⃗ false) false| v⃗ normalp v⃗ false| where C D is the drag coefficient, d p is the diameter of the particle, and v p is the particle velocity. For particle deposition, a trap condition is applied on the wall of the lung model and an escape condition is applied at all outlets of the airways, which corresponds to the exit point at generation six. , This ensures that when a particle strikes the inner wall of the lung, the fate of that particle will be considered trapped or deposited at that point of the airway.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lagrangian approach is used to simulate the particle TD in the lung airways. The dynamics of each particle are controlled through the force balance equation: d u⃗ p d t = F D false( u⃗ u⃗ normalp false) + g⃗ ρ p false( ρ normalp ρ false) where u and u p represent the velocity of continuous and discrete phases, respectively, g is the gravitational acceleration, ρ p is particle density, which is taken as 1100 kg/m 3 . F D ( u⃗ – u⃗ p ) represents the drag force per particle mass, and the F D for the spherical particle is determined using the following relation: F D = 1 2 C D π d p 2 4 ρ false( v⃗ normalp v⃗ false) false| v⃗ normalp v⃗ false| where C D is the drag coefficient, d p is the diameter of the particle, and v p is the particle velocity. For particle deposition, a trap condition is applied on the wall of the lung model and an escape condition is applied at all outlets of the airways, which corresponds to the exit point at generation six. , This ensures that when a particle strikes the inner wall of the lung, the fate of that particle will be considered trapped or deposited at that point of the airway.…”
Section: Methodsmentioning
confidence: 99%
“…The dynamics of each particle are controlled through the force balance equation: where u and u p represent the velocity of continuous and discrete phases, respectively, g is the gravitational acceleration, ρ p is particle density, which is taken as 1100 kg/m 3 . 51 53 F D ( u⃗ – u⃗ p ) represents the drag force per particle mass, and the F D for the spherical particle is determined using the following relation: where C D is the drag coefficient, d p is the diameter of the particle, and v p is the particle velocity. For particle deposition, a trap condition is applied on the wall of the lung model and an escape condition is applied at all outlets of the airways, which corresponds to the exit point at generation six.…”
Section: Methodsmentioning
confidence: 99%
“…This aerosol is in the form of a diverging stream of tiny droplets that are in the diameter range from 3 µm to 6 µm such that patients can inhale them deep into lungs to treat a variety of diseases. This therapy is called inhalation therapy, also known as the pulmonary route of drug administration [2]. There are different types of nebulizers available on the market; the research reported in this paper concerns the operation of a vibrating mesh nebulizer (VMN).…”
Section: Introductionmentioning
confidence: 99%